2013
DOI: 10.1016/j.celrep.2013.04.035
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Differences between Normal and Glioma-Derived Glial Progenitor Cells Identify a Core Set of Dysregulated Genes

Abstract: SUMMARY Glial progenitor cells (GPCs) are a potential source of malignant gliomas. We used A2B5-based sorting to extract tumorigenic GPCs from human gliomas spanning WHO grades II-IV. mRNA profiling identified a cohort of genes that distinguished tumor-initiating progenitor cells (TPCs) from A2B5+ GPCs isolated from normal white matter. A core set of genes and pathways was substantially dysregulated in A2B5+ TPCs, that included the transcription factor SIX1, and its principal co-factors, EYA1 and DACH2. shRNAi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…Recent transcriptomic profiling studies have revealed that NG2 cells express a number of genes previously considered as neuron-specific genes (Table 1). Notably, Calretinin (Calb2) and Doublecortin (Dcx) used in previous NG2 cell fate and lineage analyses (He et al, 2001; Clarke et al, 2012; Tsoa et al, 2014; Jablonska et al; 2010 Dayer et al, 2005) as well as a number of genes encoding presynaptic terminal proteins are detected at significant levels in NG2 cells in five microarray and one RNA-sequence databases (Nielsen et al, 2006; Cahoy et al, 2008; Lau et al, 2008; Wang et al, 2013; Auvergne et al, 2013; Zhang et al, 2014; Moyon et al, 2015). Other genes that are actively transcribed in telencephalic NG2 cells include the interneuron proteins Gephyrin and Gad1, which may reflect their developmental history.…”
Section: The Fate Of Ng2 Cells In the Normal Developing And Maturementioning
confidence: 99%
“…Recent transcriptomic profiling studies have revealed that NG2 cells express a number of genes previously considered as neuron-specific genes (Table 1). Notably, Calretinin (Calb2) and Doublecortin (Dcx) used in previous NG2 cell fate and lineage analyses (He et al, 2001; Clarke et al, 2012; Tsoa et al, 2014; Jablonska et al; 2010 Dayer et al, 2005) as well as a number of genes encoding presynaptic terminal proteins are detected at significant levels in NG2 cells in five microarray and one RNA-sequence databases (Nielsen et al, 2006; Cahoy et al, 2008; Lau et al, 2008; Wang et al, 2013; Auvergne et al, 2013; Zhang et al, 2014; Moyon et al, 2015). Other genes that are actively transcribed in telencephalic NG2 cells include the interneuron proteins Gephyrin and Gad1, which may reflect their developmental history.…”
Section: The Fate Of Ng2 Cells In the Normal Developing And Maturementioning
confidence: 99%
“…Both SIX1 and EYA are overexpressed in multiple cancer types including ovarian 53, 75 , breast 77 , glioblastomas 86 , leukemia 81 , and Wilms’ tumor 72 . Moreover, we found that overexpression of either SIX1 or EYA commonly correlated with recurrence, metastasis, and a decreased overall survival in a variety of tumor types, using the Oncomine cancer microarray database 19 .…”
Section: The Role Of the Six1/eya Interaction In Tumorigenesis Andmentioning
confidence: 99%
“…Liu et al, 2011). As A2B5-expressing GSCs become more mesenchymal with grade (Auvergne et al, 2013), it is possible that cell-surface proteins on GSCs change during the disease progression or following therapy (Bhat et al, 2011, 2013; K. V Lu et al, 2012; Mao et al, 2013).…”
Section: Relationship Between Glioma Stem Cells and Glial Progentiorsmentioning
confidence: 99%
“…The authors show that the WNT inhibitor secreted frizzled-related protein 1 (SFRP1) effectively reduced proliferation and self-renewal of GSCs (Sandberg et al, 2013). Furthermore, WNT components are more prominently expressed in A2B5+ cells isolated from GBM versus lower-grade gliomas (Auvergne et al, 2013). During normal development, WNT influence the timing and efficacy of OPC generation in the telencephalon (Langseth et al, 2010).…”
Section: Relationship Between Glioma Stem Cells and Glial Progentiorsmentioning
confidence: 99%
See 1 more Smart Citation